METOPROLOL AND CARVEDILOL IN THERAPY OF ACUTE MYOCARDIAL INFARCTION: WHEN AND WHICH DRUG TO PREFER - B. N. Garifullin; A. N. Zakirova; F. S. Zarudij (Столичная издательская компания, 2016)
Results of large randomized clinical trails on beta-blockers therapy of myocardial infarction (MI) with ST segment elevation (COMMIT/CCS-2, CAPRICORN) are analyzed. Last changes in guidelines regarding beta-blockers prescription to patients with MI are presented. Data of the studies comparing influence of metoprolol tartrate and carvedilol on MI pathogenesis are presented. Possible indications and treatment schemes for carvedilol in patients with acute MI are discussed.